PERAN SERTIFIKASI KOMPETENSI TERHADAP KARIR KARYAWAN PT PETROKIMIA GRESIK - susetyorini, susetyorini susetyorini; Andono, Wahyu (Fakultas Ekonomi Universitas Gresik, 2018)
To support the level of success in conducting employee performanceassessment activities, a method is needed. One of them is by using thecompetency certification method. Where competence is the ability tocarry out tasks in the workplace which includes the application of skillsthat are supported by knowledge and attitudes in accordance with theconditions required. The purpose of this study was to determine howmuch influence the competency certification (Skill, Knowledge andAttitude) has on the careers of employees of PT Petrokimia Gresik. Theresearch method used is descriptive with a qualitative approach. Theresults of the study found that certification activities of competencies andresults assessment of competency tests proved to be able to supportimprovement competence, professionalism and career path of employeesof PT Petrokimia Gresik. Employees also feel satisfied after takingcertification competence. They consider it to be the right method ofassessing potential because it is carried out by assessors from externalparties. Simulation or test given according to actual conditions so thatthe results of the assessment can be used as material for self-reflectionfor employees.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475654